Student responses to instructional activities in the literature in English classroom - Wan, Irene Yoke Quin (2011)
The main purpose of the study was to examine students’ responses to instructional activities in the literature in English component classroom. The study was carried out through a detailed investigation of four research questions: 1) What are students’ responses to the literature in English component? 2) What are the types of instructional activities carried out during the literature in English component lessons? 3) How do students respond to the types of instructional activities carried out during the literature in English component lessons? 4) What are students’ preferences to the types of instructional activities used in the literature in English component lessons? These questions were continuously addressed throughout the study with the specific concern of investigating students’ responses to activities used in the literature in English component classroom and linking students’ responses to actual classroom practices in the literature in English component classroom in secondary schools in Malaysia. A mixed method research methodology was selected for the present study. Data was gathered and generated from Form 4 students from four government secondary schools. The participants were selected based on the criterion of purposive sampling. The data collection method to achieve the purpose of this study was questionnaire, structured interview and document review. The questionnaire was administered individually to each participant in each respected school. This is followed by a random sampling of participants in each school for the structured interview in which further questions which required a more discussive approach were raised by the researcher. The interviews were recorded using digital audio recorder. In addition, documents in the form of teachers’ lesson plans, syllabus and students’ products were also analysed. The credibility of the study were ensured through member checks, triangulation of data source and audit trail. The findings were further conceptualized to portray students’ preferences and practices. Findings showed students’ interest to the literature in English component and reasons students like and dislike the component. Findings also showed that students’ interest to different types of instructional activities used in the component depended on how much the activity helps them understand the texts that they are reading, as well as, the frequency of the activities conducted in the component’s classroom. Instructional activities that were too often conducted in the component’s classroom tend to make students lose interest in completing them. Students’ practices while learning the literature in English component is obtained based on their interest on the types of instructional activities according to different multiple intelligences and focus in relation to the literature teaching models.